Correlation of Morphological Characteristics of Nyamplung Seedling (Calophyllum inophyllum L) with The Performance at Field Condition - Ratna , Ratna Damayanti Siantur; Dede , Dede J Sudrajat (Jurnal Wasian, 2019)
The aim of this research is to assess the correlation of morphological characteristics of nyamplung seedling (Calophyllum inophyllum L) on field growth of two years age after outplanting in Parungpanjang, Bogor. Three seedlots collected from Carita, Pangandaran and Purworejo were grown in seedbeds with different ages (four months and six months). The seedlings are mixed and grouped according to their height and root collar diameter. Each group of seedlings is divided into 5 height classes and each class is divided into two diameter classes, so there are 10 classes of seed morphology. The parameters of seedling were observed on sturdirness quotient, dry weight, root length, shoot-root ratio, and number of leaves. The seedlings were planted in randomized completely block design (three seeds origins, 10 morphological class, three blocks, 30 seedlings per block). Seedling survival, height, and root collar diameter growth were assessed on two years after outplanting. The result showed that morphological classification affected on seedling survival, height and root collar diameter growth. Seedling height and root collar diameter were significantly correlated with other parameters and also with field growth. Two-year-old Nyamplung on field can grow significantly if we use seedling with a height above 31 cm and a diameter more than 5.1 mm. In addition, the ratio of height and diameter and seed quality index are become important consideration in seed selection.